Comprehension of academic texts: role of executive functions and vocabulary: Comprehension of academic texts: role of executive functions and vocabulary - Ramírez-Peña, Paula; Pérez-Salas, Claudia Paz; Riffo Ocares , Bernardo; Cerdán Otero, Raquel (Nueva Revista del Pacífico, 2023)
Comprehension of academic texts is often a complex activity for university students during their first year of studies. This activity may be associated with a higher cognitive demand when reading in digital support and in the presence of distractors. Thus, the general objective of this research was to analyze the role of four executive functions (inhibition, goal setting, working memory and processing speed) in the comprehension of academic texts, together with the role of vocabulary. 62 first-year university students participated in an experimental study in which the effect of inhibition and goal setting on academic text comprehension was analyzed. To determine the effect of the distractor on reading comprehension, an eye tracker was used during reading. The experimental task was complemented with the measure of working memory, processing speed and vocabulary. From the results we conclude that inhibition and goal setting influence comprehension when reading is interrupted by distractors. In addition, we conclude that working memory and processing speed are not related to comprehension, in contrast to vocabulary which correlates positively and significantly with the comprehension of academic texts in first-year university students.